Cement-based material with photocatalytic function, coating, casting body and preparation method
By dispersing molybdenum disulfide nanoflowers in cement-based materials, the problems of insufficient building performance and complex preparation methods of existing cement-based materials are solved, and the efficient photocatalytic and mechanical properties of the materials are improved.
Patent Information
- Application Number
- CN202411676019.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
The building performance of cement-based materials with existing photocatalytic functions needs to be improved, and the preparation method is complicated.
By uniformly dispersing molybdenum disulfide nanoflowers in the cement-based material, the nanoflowers are prepared by hydrothermal method, and mixed with silicate cement, and directly participate in the hydration reaction to form a cement-based material with photocatalytic function.
It improves the density and durability of cement-based materials, enhances its self-cleaning and degradation functions of dyes, while simplifying the preparation process and improving the hydration rate and mechanical properties.
Smart Images

Figure CN119569393A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a cement-based material, a coating, a casting body and a preparation method thereof with a photocatalytic function. Background Art
[0002] Sewage treatment plants are important facilities for urban and industrial wastewater treatment. Their main task is to remove harmful substances from sewage through physical, chemical and biological methods to meet discharge standards. However, traditional sewage treatment processes face many challenges. First, the walls of water treatment pools are prone to accumulate various pollutants, such as algae, bacteria and organic matter, which not only affect the treatment effect but also increase maintenance costs. Secondly, conventional cleaning methods such as high-pressure water gun flushing and the use of chemical cleaning agents are not only time-consuming and labor-intensive, but may also cause secondary pollution to the environment.
[0003] Photocatalytic materials can effectively decompose organic pollutants and have a self-cleaning function, that is, the pollutants on the surface of the photocatalytic material will be decomposed and carried away by the water flow, thereby keeping the surface clean. Photocatalytic materials have been widely used in the fields of air purification, water treatment and self-cleaning surfaces. The patent with publication number CN 115646475 B discloses an innovative method for preparing cement-based materials, which aims to enhance its photocatalytic ability under natural light conditions by wrapping a titanium dioxide film on hollow glass microspheres. This technology uses a sol-gel method to effectively avoid the agglomeration problem of titanium dioxide powder, increase the specific surface area of the catalyst, and thus improve the efficiency of light utilization. However, although this method solves the agglomeration problem of titanium dioxide nanopowder with photocatalytic function, hollow glass microspheres are used as intermediate media, which will affect the hydration performance and bonding strength of cement-based materials. At the same time, the preparation process of existing cement-based materials with added titanium dioxide is cumbersome. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a cement-based material, coating, casting and preparation method with photocatalytic function, which solves the technical problems that the construction performance of the existing cement-based materials with photocatalytic function needs to be improved and the preparation method is complicated.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] In a first aspect, an embodiment of the present invention provides a cement-based material with photocatalytic function, which comprises cement-based dry powder, wherein the cement-based dry powder contains, by weight: 1-1.5 parts of molybdenum disulfide nanoflowers and 9-19 parts of silicate cement.
[0009] As a preferred embodiment of the present invention, the cement-based material, the molybdenum disulfide nanoflower has a particle size of 450-500 nm and a specific surface area of 31.4-60 m 2 / g.
[0010] As a preferred embodiment of the present invention, the cement-based material is a slurry, which is obtained by mixing and dispersing cement-based dry powder and water accounting for 0.45-0.55 times the mass of the cement-based dry powder; wherein the cement-based dry powder is composed of 9-19 parts of silicate cement and 1 part of molybdenum disulfide nanoflowers.
[0011] Among them, the cement-based material slurry adopts the above ratio, which can not only meet the requirements of catalysis and construction performance, but also reduce the amount of molybdenum disulfide nanoflowers and save costs.
[0012] As a preferred embodiment of the present invention, the cement-based material and the molybdenum disulfide nanoflowers are prepared according to the following method: sodium molybdate, thioacetamide and water are fully stirred and mixed in a mass ratio of 5:4:1.2 to obtain a reaction stock solution; the reaction stock solution is subjected to a constant temperature reaction at a pressure of 10-50MPa and 180-200°C for 16-18h, and the black solid product is washed, dried and ground and dispersed to obtain molybdenum disulfide nanoflowers.
[0013] Among them, the method used to prepare molybdenum disulfide nanoflowers is simple and can directly prepare nanoflowers that meet the particle size and high purity requirements without additional treatment and can directly participate in subsequent hydration reactions.
[0014] In a second aspect, an embodiment of the present invention provides a method for preparing the cement-based material according to the first aspect, comprising the following steps:
[0015] S1, preparing molybdenum disulfide nanoflowers by hydrothermal reaction of a molybdenum source, a sulfur source and water;
[0016] S2, evenly dispersing the molybdenum disulfide nanoflowers in water to prepare a mixed liquid;
[0017] S3, mixing the mixed liquid with silicate cement, stirring evenly, to obtain the cement-based material.
[0018] As a preferred embodiment of the present invention, the preparation method of the cement-based material, in S1, the hydrothermal reaction to prepare molybdenum disulfide nanoflowers is specifically as follows: sodium molybdate, thioacetamide and water are fully stirred and mixed in a mass ratio of 5:4:1.2 to obtain a reaction stock solution;
[0019] The reaction stock solution is reacted at a constant temperature of 180-200° C. at a pressure of 10-50 MPa for 16-18 hours, and the black solid product is washed, dried, ground and dispersed to obtain molybdenum disulfide nanoflowers.
[0020] As a preferred embodiment of the present invention, in the method for preparing the cement-based material, in S1, the process of washing the black solid product is to cool to room temperature after the reaction is completed, collect the black precipitate by centrifugation, and wash it three times alternately with deionized water and anhydrous ethanol; the black solid product is vacuum dried for 36-40 hours.
[0021] Among them, washing ensures the purity of the reactants, vacuum drying is used to further ensure the purity of the crystals, and ultimately the catalytic performance of molybdenum disulfide nanoflowers is ensured.
[0022] As a preferred embodiment of the present invention, in the method for preparing cement-based materials, in S2, the molybdenum disulfide nanoflowers are dispersed into water by ultrasonic wave. The molybdenum disulfide nanoflowers are fully dispersed into water to ensure that the subsequent molybdenum sulfide nanoflowers can be evenly distributed in the silicate cement to ensure that the catalytic function is exerted.
[0023] In a third aspect, an embodiment of the present invention provides a cement-based coating or casting having a photocatalytic function, which is prepared by applying the cement-based material described in the first aspect or the cement-based material prepared by the preparation method described in the second aspect on a base surface or casting it in a mold, and curing it to obtain a cement-based coating or casting having a photocatalytic function.
[0024] As a preferred embodiment of the present invention, in the method for preparing the cement-based coating or casting, the cement-based coating is sealed and cured one day after the cement-based material is applied;
[0025] The cement-based casting body is sealed and cured after the mold is removed one day after the cement-based material is cast;
[0026] Among them, the sealing maintenance temperature is 20-25℃;
[0027] The cement-based coating or casting is used for the walls of sewage treatment tanks.
[0028] (III) Beneficial effects
[0029] The beneficial effects of the present invention are as follows: the cement-based material, coating, casting and preparation method with photocatalytic function of the present invention, in the cement-based material, the molybdenum disulfide nanoflowers are evenly dispersed in the silicate cement, which can directly participate in the hydration reaction of the cement-based material, and the evenly dispersed molybdenum disulfide nanoflowers can fill the microscopic pores of the cement-based material after hydration, play a physical filling effect, and help to improve the compactness and durability of the hydrated material. At the same time, the molybdenum disulfide nanoflowers can promote the hydration reaction, and through the action of chemical bonds, it is completely solidified in the cement-based material, avoiding the exfoliation of the molybdenum disulfide nanoflowers and the failure of photocatalysis under external factors, thereby ensuring the good catalytic effect of the cement-based material. 9-19 parts of silicate cement and 1-1.5 parts of molybdenum disulfide nanoflowers, wherein the amount of molybdenum disulfide nanoflowers can not only ensure the photocatalytic effect, but also the best bonding state with silicate cement, ensuring that the formed cement-based material has good mechanical properties. Compared with the existing technology, by directly introducing molybdenum disulfide nanoflowers into cement-based materials as photocatalysts, the self-cleaning and dye degradation functions of the materials are increased, while the hydration rate and mechanical properties of cement are improved, which is a green and sustainable building material. The preparation method of the cement-based material with photocatalytic function is simple and efficient.
[0030] The use of MoS2 nanoflowers with a particle size of 450-500nm helps to promote hydration reactions and fill microscopic pores in cement-based materials. The specific surface area of MoS2 nanoflowers is 31.4-60m 2 / g, high catalytic efficiency.
[0031] The molybdenum disulfide nanoflowers are dispersed into water by ultrasound and then mixed with silicate cement for reaction, so that the molybdenum disulfide nanoflowers can be fully and evenly dispersed to ensure the uniformity of the reaction between the molybdenum disulfide nanoflowers and silicate cement.
[0032] Cement-based materials are used for the walls of sewage treatment pools, which can effectively decompose the dirt and microorganisms brought by the wall surface during the process of contact with sewage, and can also help decompose the organic dyes in the sewage, thereby improving the self-cleaning ability of the sewage treatment pool walls and the sewage treatment efficiency. At the same time, because the molybdenum disulfide nanoflowers are evenly dispersed throughout the cement-based material, the cement-based material on the surface is damaged and the cement-based material inside is exposed, which will also not affect the function of the wall. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope micrograph of the molybdenum disulfide nanoflower prepared in Example 1;
[0034] Figure 2 The compressive strength bar graph of the cement-based materials prepared in Comparative Example 1, Example 2 and Example 3 after curing for 1 to 28 days;
[0035] Figure 3 is a cumulative curve diagram of mercury intrusion into pore volume of cement-based materials prepared in Comparative Example 1, Example 2 and Example 3 on the 28th day of curing;
[0036] Figure 4 The UV-visible absorption spectrum of the cement-based material prepared in Example 3 for the adsorption of Rhodamine 6G;
[0037] Figure 5 The UV-visible absorption spectrum of the cement-based material prepared in Comparative Example 1 upon adsorption of Rhodamine 6G;
[0038] Figure 6 It is a curve diagram of the adsorption efficiency of Rhodamine 6G by the cement-based materials prepared in Comparative Example 1 and Example 3. DETAILED DESCRIPTION
[0039] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0040] The cement-based material, coating, casting and preparation method with photocatalytic function proposed in the embodiment of the present invention are aimed at the need to improve the construction performance of the existing cement-based material with photocatalytic function and the cumbersome technical problems of the preparation method; the molybdenum disulfide nanoflowers are evenly dispersed in the silicate cement in the cement-based material, which can directly participate in the hydration reaction of the cement-based material, and the evenly dispersed molybdenum disulfide nanoflowers can fill the microscopic pores of the cement-based material after hydration, play a physical filling effect, and help to improve the compactness and durability of the hydrated material. At the same time, the molybdenum disulfide nanoflowers can promote the hydration reaction, and through the action of chemical bonds, it is completely solidified in the cement-based material, avoiding the exfoliation of the molybdenum disulfide nanoflowers and the failure of photocatalysis under external factors, thereby ensuring the good catalytic effect of the cement-based material. 9-19 parts of silicate cement and 1-1.5 parts of molybdenum disulfide nanoflowers, wherein the amount of molybdenum disulfide nanoflowers can not only ensure the photocatalytic effect, but also the best bonding state with silicate cement, so as to ensure that the formed cement-based material has good mechanical properties. Compared with the existing technology, by directly introducing molybdenum disulfide nanoflowers into cement-based materials as photocatalysts, the self-cleaning and dye degradation functions of the materials are increased, while the hydration rate and mechanical properties of cement are improved, which is a green and sustainable building material. The preparation method of the cement-based material with photocatalytic function is simple and efficient.
[0041] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0042] Example 1
[0043] This embodiment provides a method for preparing molybdenum disulfide nanoflowers, which specifically includes the following steps:
[0044] (1) 500 mg of sodium molybdate and 400 mg of thioacetamide were taken, respectively, and fully mixed into 120 mL of deionized water. The solution was stirred with a magnetic stirrer for 15 minutes to prepare a mixed solution;
[0045] (2) The mixed solution was transferred to a 200 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at a constant temperature of 10 MPa and 180°C for 16 h. After the reaction, the autoclave was cooled to 20°C and the precipitate was collected by centrifugation;
[0046] (3) The precipitate was washed alternately with deionized water and anhydrous ethanol for three times, and then the precipitate was placed in a vacuum drying oven for 36 hours to obtain a black solid. The black solid was thoroughly ground with a mortar to finally obtain molybdenum disulfide nanoflowers.
[0047] The MoS2 nanoflowers synthesized in this example were tested and analyzed using a scanning electron microscope (SEM) at an accelerating voltage of 200 kV. The morphology and size of the MoS2 nanoflowers were observed using a scanning electron microscope. Figure 1 As shown in the figure, the prepared MoS2 nanoflowers have a petal-like structure, excellent electrical, physical, chemical and mechanical properties, uniform particle size distribution, an average particle size of 450-500nm, an average lattice fringe spacing of 0.48nm, and a specific surface area of 31.4m 2 / g.
[0048] The crystal phase purity of molybdenum disulfide obtained by X-ray diffraction is high, and no diffraction peak of the impurity phase is observed.
[0049] Example 2
[0050] This embodiment provides a method for preparing a cement-based material with photocatalytic function and a casting thereof, which specifically comprises the following steps:
[0051] (1) 60 g of the molybdenum disulfide nanoflowers prepared in Example 1 were put into 600 g of water, and then effectively dispersed using an ultrasonic generator for 10 min to obtain a mixed liquid;
[0052] (2) Then pour the mixed liquid into 1140 g of ordinary Portland cement, use a mechanical stirrer to mix evenly, and pour it into a mold to form a sample;
[0053] (3) After one day, the mold was removed, and the sample was wrapped with a film and placed at a constant temperature of 20° C. for sealed curing for 28 days to prepare a cement-based material with photocatalytic function.
[0054] The compressive strength of the prepared cement-based material was tested according to the ASTM C349 method. The results are shown in Table 2.
[0055] The prepared cement-based material was subjected to pressure-injection porosity measurement using the cumulative pore volume test method. Specifically, the sample was subjected to pressure-injection porosity measurement using an automatic pressure-injection porosity measuring instrument, with the minimum and maximum pressures being 0.1 MPa and 414 MPa, respectively. The test results are shown in Figure 1. Figure 3 shown.
[0056] Example 3
[0057] This embodiment provides a method for preparing a cement-based material with photocatalytic function and a casting thereof, which specifically comprises the following steps:
[0058] (1) 120 g of the molybdenum disulfide nanoflowers prepared in Example 1 were put into 600 g of water, and then effectively dispersed using an ultrasonic generator for 10 min to obtain a mixed liquid;
[0059] (2) Then pour the mixed liquid into 1080g of ordinary Portland cement, use a mechanical stirrer to mix evenly, and pour it into a mold to form a sample;
[0060] (3) After 1 day, the mold was removed, and the sample was wrapped with a film and placed at a constant temperature of 25° C. for sealed curing for 28 days to prepare a cement-based material with photocatalytic function.
[0061] The compressive strength of the prepared cement-based material was tested according to ASTM C349. The results are shown in Table 2.
[0062] The prepared cement-based material was subjected to pressure-injection porosity measurement using the cumulative pore volume test method. Specifically, the sample was subjected to pressure-injection porosity measurement using an automatic pressure-injection porosity measuring instrument, with the minimum and maximum pressures being 0.1 MPa and 414 MPa, respectively. The test results are shown in Figure 1. Figure 3 shown.
[0063] The prepared cement-based material was tested for photocatalytic degradation efficiency, specifically: the organic dye Rhodamine 6G was used as the photocatalytic degradation target, and the concentration of the organic dye solution was 20 ppm. The test sample was cut into 4×4×4 mm 3 Cubes of different sizes were prepared and the contact surfaces of all samples were made consistent. A 50g cube sample was immersed in a 500mL organic dye rhodamine solution, the mixture was continuously shaken in a shaking incubator, and the sample was exposed to a UV lamp to simulate the UV intensity under natural light conditions. The supernatant was taken every 30 minutes and analyzed by UV-visible absorption spectrum using a UV / visible spectrophotometer to test the intensity of the absorption peak (λmax=523nm) of rhodamine 6G. The test results are shown in Figure 2. Figure 4 and Figure 5 shown.
[0064] Comparative Example 1
[0065] This comparative example provides a method for preparing a cement-based material and a casting thereof, which differs from Example 3 in that no molybdenum disulfide nanoflowers are added in step (1). The remaining steps are the same.
[0066] Referring to Example 3, the compressive strength test of the cement-based material prepared in this comparative example is carried out, and the results are shown in Table 2; the intrusion porosity measurement is shown in Table 2. Figure 3 As shown; Photocatalytic degradation efficiency test, the test results are as follows Figure 4 and Figure 6 shown.
[0067] For the convenience of comparison, Table 1 shows the addition amounts of the substances in Example 2, Example 3 and the comparative example.
[0068] Table 1 Amount of substances added and treatment methods in the examples and comparative examples
[0069]
[0070] Table 2 Compressive strength test results of cement-based materials
[0071] Compressive strength / MPa 1 day 3 days 28 days Example 2 14.2 29.5 49.5 Example 3 14.9 30.6 48.8 Comparative Example 1 12.4 27.2 48.1
[0072] Through the above examples and comparative examples analysis, it can be seen that:
[0073] Referring to Tables 1 and 2, at a curing age of 1 day, the compressive strength of the cement-based material of Comparative Example 1 is 12.4 MPa, while the compressive strengths of the cement-based materials of Examples 1 and 2 are 14.2 MPa and 14.9 MPa, respectively, which are 14.1% and 20.4% higher than those of Comparative Example 1, respectively. This indicates that the addition of molybdenum disulfide nanoflowers can effectively improve the early compressive strength of cement paste. With the increase of curing age, the effect of molybdenum disulfide nanoflowers on improving compressive strength gradually weakens. At a curing age of 28 days, the compressive strength of all samples is not much different, indicating that the addition of molybdenum disulfide nanoflowers has no effect on the final compressive strength of cement-based materials.
[0074] Reference Figure 3 As shown, compared with the cement-based material of Comparative Example 1, the cumulative curve of mercury intrusion into pore volume of the cement-based materials of Examples 1 and 2 moves to the left (towards the smaller pore volume). Further comparison between Example 1 and Example 2 shows that the cement-based material can refine the total pore volume after adding molybdenum disulfide nanoflowers, and the molybdenum disulfide nanoflowers have a physical filling effect, which helps to improve the density and durability of the material.
[0075] Figure 4 The UV-visible absorption spectrum of the cement-based material in Example 3 for the degradation of Rhodamine 6G. As the photocatalytic time increases, the absorption peak height of Rhodamine 6G decreases and the color of the solution gradually becomes lighter. Figure 6 When the photocatalytic time is 180 min, the adsorption efficiency of the cement-based material of Example 3 for Rhodamine 6G is as high as 85.9%, and it also shows an upward trend, showing a good adsorption-catalytic effect.
[0076] Reference Figure 5 and Figure 6 As the photocatalytic time goes by, the cement-based material in Comparative Example 1 without adding molybdenum disulfide nanoflowers has a small decrease in the absorption peak height of Rhodamine 6G in the UV-visible absorption spectrum of Rhodamine 6G degradation due to the physical adsorption effect of the surface voids, and the color change of the solution is not obvious. In contrast, in the initial stage of photocatalysis, the rate of increase of the adsorption efficiency of Rhodamine 6G in the solution by the cement-based material of Example 3 is significantly higher than that of Comparative Example 1, and the adsorption efficiency of Rhodamine 6G in the solution by Comparative Example 1 is also much lower than that of Example 3 as the photocatalytic time goes by.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cement-based material with photocatalytic function, characterized in that: The invention comprises cement-based dry powder, wherein the cement-based dry powder contains, by weight, 1-1.5 parts of molybdenum disulfide nanoflowers and 9-19 parts of silicate cement.
2. The cement-based material according to claim 1, characterized in that The particle size of the molybdenum disulfide nanoflower is 450-500nm, and the specific surface area is 31.4-60m 2 / g.
3. The cement-based material according to claim 1 or 2, characterized in that: The cement-based material is a slurry obtained by mixing and dispersing cement-based dry powder and water accounting for 0.45-0.55 times the mass of the cement-based dry powder; wherein the cement-based dry powder is composed of 9-19 parts of silicate cement and 1 part of molybdenum disulfide nanoflowers.
4. The cement-based material according to claim 1, characterized in that The molybdenum disulfide nanoflowers are prepared by the following method: sodium molybdate, thioacetamide and water are fully stirred and mixed in a mass ratio of 5:4:1.2 to obtain a reaction stock solution; The reaction stock solution is reacted at a constant temperature of 180-200° C. at a pressure of 10-50 MPa for 16-18 hours, and the black solid product is washed, dried, ground and dispersed to obtain molybdenum disulfide nanoflowers.
5. A method for preparing a cement-based material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, preparing molybdenum disulfide nanoflowers by hydrothermal reaction of a molybdenum source, a sulfur source and water; S2, evenly dispersing the molybdenum disulfide nanoflowers in water to prepare a mixed liquid; S3, mixing the mixed liquid with silicate cement, stirring evenly, to obtain the cement-based material.
6. The method for preparing the cement-based material according to claim 5, characterized in that: In S1, the hydrothermal method for preparing molybdenum disulfide nanoflowers is as follows: sodium molybdate, thioacetamide and water are fully stirred and mixed in a mass ratio of 5:4:1.2 to obtain a reaction stock solution; The reaction stock solution is reacted at a constant temperature of 180-200° C. at a pressure of 10-50 MPa for 16-18 hours, and the black solid product is washed, dried, ground and dispersed to obtain molybdenum disulfide nanoflowers.
7. The method for preparing a cement-based material according to claim 6, characterized in that: In S1, The process of washing the black solid product is as follows: after the reaction is completed, the product is cooled to room temperature, the black precipitate is collected by centrifugation, and then washed three times with deionized water and anhydrous ethanol alternately; The black solid product was dried under vacuum for 36-40 h.
8. The method for preparing a cement-based material according to claim 5, characterized in that: In S2, MoS2 nanoflowers are dispersed into water by ultrasound.
9. A cement-based coating or casting having a photocatalytic function, characterized in that: The cement-based material described in any one of claims 1 to 4 or the cement-based material prepared by the preparation method described in any one of claims 5 to 8 is applied on a base surface or cast in a mold, and then cured to obtain a cement-based coating or casting with photocatalytic function.
10. The cement-based coating or casting according to claim 9, characterized in that: The cement-based coating is sealed and cured one day after the cement-based material is applied; The cement-based casting body is sealed and cured after the mold is removed one day after the cement-based material is cast; Among them, the sealing maintenance temperature is 20-25℃; The cement-based coating or casting is used for the walls of sewage treatment tanks.
Citation Information
Patent Citations
A secondary supported photocatalytic cement-based material and preparation method thereof
CN115646475B
Cited By
Repairing agent mixed powder and preparation method thereof
CN121159190A